The Construction Of Teaching Patience In Islam; Energy Find Solutions In Problems - Syairozi, Ishak (CV ODIS, 2023)
Problems in human life are inevitable inevitability for every individual. Life is a process that cannot be separated from trials and problems as mentioned in the word of Allah sura al-Baqarah/2: 155. How is patient teaching interpreted to be the energy of finding solutions to problems? The answer to this research is expected to provide a description of the meanings of patience in practical life so that readers can find solutions to the problems and trials they face. The methodology used is a qualitative approach, by doing two actions, namely; First (TP1), a literature study of the meaning and meaning of patience in the perspective of the Qur'an, and on the views of experts, both in books and Ilmiyah journals. The second (TP2), uses a qualitative approach with the Grounded Theory method, which aims to build a theoretical analysis of the appropriate data and relevant to the practical patience in life. This method is a research strategy in which the researcher produces a general and abstract theory of a certain process, action, or interaction derived from the views of participants. The results of the research are expected to be able to provide solutions to unravel the problems of many people with patient practice which becomes energy in dealing with problems. In deepening the concept of patience, the view of patience appears to be energy when interpreted as; The Power of facing reality, Grateful in the process, Tenacity of finding solutions, and Serenity cultivates energy. Finally, with the study in this study, it is understood that the teaching of patience in Islam is related to the reward (grace) prepared by Allah.